Formulation of Set Covering Problem Using Myopic Algorithm and Greedy Reduction Algorithm in Determining the Location of Temporary Landfills in Semambu Island Village, Ogan Ilir Regency, South Sumatra - Fitri Maya Puspita; Sisca Octarina; Laila Hanum; Chatrin Yohana Simamora; Helena Valenta Br Kemit; Evi Yuliza (Science and Technology Indonesia, 2023)
This study discusses Set Covering Problem (SCP) in designing the optimal temporary waste disposal site (TWDS) in Semambu Island Village using the Myopic Algorithm (MA) and Greedy Reduction Algorithm (GRA). The analysis was carried out and compared using a maximum distance of 500m and 1000m to get the best solution from two methods. The results of the p Median Problem by LINGO 13.0 software and MA with a maximum distance of 500m show the same TWDS location, namely Working Area (WA) 1, 2, 3, 4, 5, and 6 with the location of the candidate TWDS being at TWDS 2 WA 1, TWDS 1 WA 2, TWDS 2 WA 3, and TWDS 2 WA 5. For 1000m, it will be the location of the candidate’s TWDS being at TWDS 2 WA 1, TWDS WA 2, and TWDS 2 WA 3. Using GRA, results were obtained will be 4 TWDS, namely TWDS 2 Hamlet 1, TWDS 1 Hamlet 2, TWDS 2 Hamlet 3, TWDS 2, Hamlet 5. Then using GRA, 2 solutions are obtained, namely columns 2 and 5 which dominate. Column 2 nomination are Hamlets 1, 2, 3, and 6. Column 5 which dominates will be Hamlets 1, 3, 5, and 6.